Independent effect of fat-to-muscle mass ratio at bioimpedance analysis on long-term survival in patients receiving surgery for pancreatic cancer - Sandini, Marta; Paiella, Salvatore; Cereda, Marco; Angrisani, Marco; Capretti, Giovanni; Famularo, Simone; Giani, Alessandro; Roccamatisi, Linda; Fontani, Andrea; Malleo, Giuseppe; Salvia, Roberto; Roviello, Franco; et al. (Frontiers in Nutrition, 2023)
Introduction: Malnutrition and alteration of body composition are early features in pancreatic cancer and appear to be predictors of advanced stages and dismal overall survival. Weather specific patient characteristics measured at the preoperative bioimpedance analysis (BIA) could be associated with long term outcomes following curative resection has not been yet described. Methods: In prospective multicenter study all histologically proven resected pancreatic cancer patients were included in the analysis. BIA was measured for all patients on the day before surgery. Demographics, perioperative data, and postoperative outcome were prospectively collected. Patients who experienced 90-day mortality were excluded from the analysis. Survival data were obtained through follow-up visit and phone interviews. Bioimpedance variables were analyzed according to the overall survival at the Kaplan-Meier curves and at the uni- and multivariate cox regression model. Results: Overall 161 pancreatic cancer patients were included. Median age was 66 (60-74) years, and 27.3% received systemic neoadjuvant treatment. There were 23 (14.3%) malnourished the preoperative evaluation. Median OS was 34.0 (25.7-42.3) months. Several bioimpedance variables were associated with OS at the univariate analysis, namely the Phase Angle [HR .85, 95%CI .74-.98)], Standardized Phase Angle [HR .91, 95%CI .82-.99)], and an increased ratio between the fat and lean mass (FM/FFM) [HR 4.27, 95%CI 1.10-16.64)]. At the multivariate analysis the FM/FFM ratio was confirmed independent predictor of OS following radical resection, together with a positive lymph-nodal status. Conclusions: Alteration of body composition at the preoperative BIVA can predict dismal oncologic outcomes following pancreatic resection for cancer.